(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article explores emotional burnout as a complex psychological phenomenon resulting from prolonged exposure to stress factors. It examines the main causes and risk factors, including professional overload, emotional exhaustion, and lack of personal resources. Special attention is given to the structure of burnout syndrome, its stages, symptoms, and consequences for mental and physical health. The paper also presents modern approaches to the prevention and management of burnout aimed at enhancing stress resilience and improving quality of life.